Degradable bone filling material as well as preparation method and application thereof
Degradable bone filler materials prepared by lyophilized crystal extrusion technology, combined with silk fibroin, chitosan and biphasic calcium phosphate, solve the problems of insufficient mechanical properties, safety and biodegradability of existing bone filler materials, and achieve the goal of achieving Effective bone defect treatment.
Patent Information
- Application Number
- CN202411577093.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing bone filler materials have shortcomings in mechanical properties, safety and biodegradability, resulting in poor results in bone defect treatment.
The core skeleton structure is prepared by lyophilized crystal extrusion technology, and the porous structure and hydrogel are covered on its surface to form a degradable bone fill material.
This material has high mechanical strength, good biodegradability and safety, can quickly form a supporting structure in the body, promote bone formation, and can be equipped with drugs or cells, which is suitable for bone defect treatment.
Smart Images

Figure CN119424744A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedical technology, and in particular relates to a degradable bone filling material and a preparation method and application thereof. Background Art
[0002] Bone defect refers to a lesion in which the integrity of the bone structure is destroyed due to congenital or acquired factors. Trauma, severe infection, malignant tumors, surgical debridement of osteomyelitis, and various congenital diseases are the main causes of bone defects. Clinically, the most common site of bone defect is the tibial shaft, which is manifested as pain and limited movement at the site of the bone defect. When combined with infection, limb fever, redness, swelling, and even pus discharge may occur, eventually leading to limb shortening, amputation, and disability. Relevant surveys and studies have shown that patients with bone defects have a long recovery period, a high disability rate, and require high postoperative treatment costs, which seriously affects the quality of life of patients with bone defects. Finding an effective way to treat bone defects has always been an important problem that has plagued orthopedic clinics.
[0003] Bone filling materials have become an indispensable means of treating bone defects. They can fill the bone defect site, play a mechanical support role and promote bone formation. Bone filling materials generally require good biocompatibility, appropriate biodegradability, certain biomechanical strength and plasticity, and also need to have a certain ability to induce or guide tissue regeneration. However, existing bone filling materials have disadvantages such as poor mechanical properties, and the inability of support and porous structure to coexist. If its mechanical strength and support performance need to be improved, it is often achieved by adding cross-linking agents in the prior art. Traditional chemical cross-linking agents themselves may have biological toxicity. After the material is implanted in the body, it may be released and have adverse effects on surrounding tissues, such as inducing inflammatory reactions and cytotoxicity. At the same time, the use of cross-linking agents will reduce the biosafety and degradability of the overall material. For bone filling materials that need to be gradually absorbed and replaced by the human body, too low biodegradability may cause the material to remain in the body for a long time, which is not conducive to the regeneration and repair of bone tissue.
[0004] Therefore, developing a bone filling material with high biosafety, rapid molding, good biodegradability and excellent mechanical strength is of great significance for the treatment of bone defects. Summary of the invention
[0005] The problem to be solved by the present invention is to provide a degradable bone filling material and a preparation method and application thereof, so as to solve the problem of poor mechanical properties, safety and biodegradability of the bone filling material.
[0006] The technical solution adopted to solve the technical problem is to provide a method for preparing a degradable bone filling material, comprising the following steps:
[0007] (1) mixing the silk fibroin solution, chitosan solution and base glue and adding biphasic calcium phosphate, mixing under heating conditions and then freezing and freeze-drying, taking out and soaking in water and placing it in a mold and freeze-drying again to obtain a core skeleton structure;
[0008] (2) separately taking a silk fibroin solution, a chitosan solution containing methacryloyl RGD peptide and a base gel, mixing them evenly and adding biphasic calcium phosphate, mixing them evenly under heating conditions, covering the surface of the core skeleton structure, and freezing and freeze-drying them in sequence, taking them out and soaking them in water, freezing and freeze-drying them again, so as to obtain a porous skeleton structure;
[0009] (3) The surface of the porous skeleton structure is covered with hydrogel to obtain a degradable bone filling material.
[0010] The beneficial effects of the technical scheme adopted in the present invention are as follows: in the present invention, the raw materials are first mixed and then heated and mixed, and then frozen for the first freeze-drying. After being taken out and soaked in water, they are immediately freeze-dried for the second time in a limited space (mold) without being frozen. Under this condition, water will quickly form ice crystals with a large volume. Due to the limited freeze-drying space, the material can form a core skeleton structure with a diameter of 0.7 to 3 mm under the squeezing of ice crystals. On this basis, there is no need to add a cross-linking agent, and according to the characteristics of the material's own components, a core skeleton structure with sufficient mechanical support properties can be formed by relying on physical cross-linking and protein covalent bonding, thereby avoiding the risk of the use of cross-linking agents affecting the biocompatibility and safety of the material. Another raw material is taken, heated and mixed, and then covered on the surface of the core skeleton structure for freezing and freeze-drying. Among them, the methacrylylated RGD peptide is added to chitosan to prepare a porous skeleton structure, which helps bone formation-related cells to adhere to the porous structure of the material, and then facilitates the material to gradually fuse with the local in situ bone tissue of the bone defect during the growth, differentiation and metabolism of bone formation-related cells after implantation, and finally completes the effect of bone defect repair. At the same time, the methacrylylated RGD peptide can play a cross-linking role between the material skeleton / porous structure and the hydrogel material, making the material stronger; take out and fully infiltrate, freeze and freeze-dry again. This step can form a randomly distributed porous structure with a pore size of 50 to 250 μm on the surface of the core skeleton structure, which is similar to trabeculae. Then, the surface of the porous skeleton structure is covered with hydrogel, so that the degradable bone filling material of the present invention has modular loading capacity, which can realize modular drug delivery or adapt to different application requirements.
[0011] Preferably, the mass concentration of the silk fibroin solution in step (1) and step (2) is 6-8%; the mass concentration of the chitosan solution in step (1) is 1-3%; the mass concentration of the chitosan solution containing methacryloyl RGD peptide in step (2) is 1-3%.
[0012] More preferably, the mass concentration of the silk fibroin solution in step (1) and step (2) is 7%; the mass concentration of the chitosan solution in step (1) is 2%; and the mass concentration of the chitosan solution containing methacryloyl RGD peptide in step (2) is 2%.
[0013] More preferably, a silk fibroin solution with a mass concentration of 7% is prepared by the following steps: 3 g of silk and 4.6 g of anhydrous sodium carbonate powder are boiled in 6 L of deionized water for 1 hour, washed with running water overnight, and dried; the silk is then added to alcohol calcium chloride to dissolve, and polyethylene glycol is added to precipitate it, and the obtained product is freeze-dried and dissolved in water to obtain a silk fibroin solution with a mass concentration of 7%.
[0014] More preferably, the chitosan solution with a mass concentration of 2% is prepared by the following steps: 0.8 g of chitosan is added to 40 mL of deionized water, and then 160 μL of glacial acetic acid is added and magnetically stirred, and then the chitosan solution with a mass concentration of 2% is obtained after stirring evenly.
[0015] More preferably, the chitosan solution containing the methacryloyl RGD peptide is prepared by the following steps: weighing the methacryloyl RGD peptide in proportion and dissolving it in the chitosan solution.
[0016] More preferably, the biphasic calcium phosphate is prepared by ultrasonically mixing hydroxyapatite powder and tricalcium phosphate powder in a mass ratio of 55:45.
[0017] More preferably, in step (1), the material-liquid ratio of the silk fibroin solution, the chitosan solution, the base glue and the biphasic calcium phosphate is 0.7-0.8 mL: 1 mL: 1 mL: 2-4 g; in step (2), the material-liquid ratio of the silk fibroin solution, the chitosan solution containing the methacryloyl RGD peptide, the base glue and the biphasic calcium phosphate is 0.7-0.8 mL: 1 mL: 1 mL: 2-4 g; the mass concentration of the methacryloyl RGD peptide in the chitosan solution containing the methacryloyl RGD peptide is 0.01-1%.
[0018] More preferably, in step (1), the liquid ratio of silk fibroin solution, chitosan solution, base glue and biphasic calcium phosphate is 0.75 mL: 1 mL: 1 mL: 3 g; in step (2), the liquid ratio of silk fibroin solution, chitosan solution containing methacryloyl RGD peptide, base glue and biphasic calcium phosphate is 0.75 mL: 1 mL: 1 mL: 3 g; the mass concentration of methacryloyl RGD peptide in the chitosan solution containing methacryloyl RGD peptide is 1%.
[0019] Preferably, step (1) comprises the following steps: mixing the silk fibroin solution, chitosan solution and base glue and adding biphasic calcium phosphate, mixing under heating conditions of 55 to 75°C in a water bath, freezing at -55 to -200°C for 20 to 60 minutes and then freeze-drying, taking out and soaking in water for 1.5 to 2 minutes, then placing it in a mold and freeze-drying it again to obtain a core skeleton structure.
[0020] More preferably, step (1) comprises the following steps: mixing the silk fibroin solution, chitosan solution and base glue and adding biphasic calcium phosphate, mixing in a 65°C water bath, freezing at -80°C for 30 minutes and then freeze-drying, taking out and soaking in water for 2 minutes, then placing it in a mold and freeze-drying it again to obtain a core skeleton structure.
[0021] Preferably, step (2) comprises the following steps: separately taking a silk fibroin solution, a chitosan solution containing methacryloyl RGD peptide and a base glue, mixing them and adding biphasic calcium phosphate, mixing them in a water bath at 55 to 75°C and covering them on the surface of the core skeleton structure, freezing them at -55 to -200°C for 20 to 60 minutes and then freeze-drying them, taking them out and soaking them in water for 2 to 15 minutes, then freezing them at -55 to -200°C for 20 to 60 minutes and then freeze-drying them to obtain a porous skeleton structure.
[0022] More preferably, step (2) comprises the following steps: separately taking a silk fibroin solution, a chitosan solution containing methacryloyl RGD peptide and a base gel, mixing them and adding biphasic calcium phosphate, mixing them in a 65°C water bath and covering them on the surface of the core skeleton structure, freezing them at -80°C for 30 minutes and then freeze-drying them, taking them out and soaking them in water for 3 minutes, then freezing them at -80°C for 30 minutes and then freeze-drying them, to obtain a porous skeleton structure.
[0023] Preferably, the hydrogel in step (3) is a hydrogel that can carry and / or slowly release nucleic acid drugs, small molecule drugs, or can allow cells to grow, crawl, adhere, and migrate in a directional manner.
[0024] The beneficial effects of the above technical solution adopted in the present invention are: by loading and releasing nucleic acid drugs (including related carriers) or small molecule drugs through hydrogel, the degradable bone filling material has modular loading capacity; by covering the hydrogel that can allow cells to grow, crawl, adhere and migrate in a directional manner, the surface or interior of the degradable bone filling material can be loaded with cells, so that it has the potential to serve as a bone tissue organoid.
[0025] More preferably, the hydrogel in step (3) comprises methacrylated hyaluronic acid, methacrylated gelatin or thermosensitive hydrogel.
[0026] The present invention also provides a degradable bone filling material prepared by the above preparation method.
[0027] The beneficial effects of the technical scheme adopted in the present invention are as follows: the degradable bone filling material of the present invention comprises a core skeleton structure, a porous skeleton structure based on the core skeleton structure and a hydrogel covered on its surface; its skeleton structure parts are all prepared by mixing a silk fibroin solution, a chitosan solution, a base glue and a biphasic calcium phosphate, and undergoing freeze-drying, crystallization and extrusion. First, a core skeleton structure with a supporting function and strong mechanical properties is generated in a limited space, and then the above mixture is wrapped on the surface of the core skeleton structure, that is, a randomly distributed porous structure similar to trabeculae is generated based on the core skeleton structure; finally, a hydrogel is covered on its surface for loading drugs or carrying cells, and it can be used for the preparation of drugs for skeletal system diseases and bone defects; the degradable bone filling material can be degraded and absorbed by bone tissue quickly after the action, and has good biodegradability; the bone filling material of the present invention has good compressive resistance, safety and biodegradability.
[0028] The present invention also provides the use of the above-mentioned degradable bone filling material in preparing bone tissue organoid material.
[0029] Preferably, the use of the degradable bone filling material in preparing bone tissue organoid material comprises the following steps:
[0030] Bone tissue organoids are obtained by loading bone-forming cell lines or primary bone-forming related cells into the hydrogel of degradable bone filling material and culturing them through a microfluidic system.
[0031] More preferably, loading bone-forming cell lines or primary bone-forming related cells in the hydrogel of the degradable bone filling material comprises the following steps: digesting the cultured bone-forming cell lines or primary bone-forming related cells with trypsin and resuspending them in culture medium to obtain a cell suspension; then dissolving the hydrogel monomer in the cell suspension and covering it on the porous skeleton structure of the degradable bone filling material for photo-crosslinking.
[0032] More preferably, the bone-forming cell lines or primary bone-forming related cells include preosteoblast cell line MC3T3-E1, mesenchymal stem cell line C3H10T1 / 2, primary adipose-derived mesenchymal stem cells ADSC and primary bone marrow-derived mesenchymal stem cells BMSC.
[0033] The present invention also provides the use of the above-mentioned degradable bone filling material in the preparation of medicines or preparations for treating skeletal system diseases.
[0034] The present invention also provides the use of the above-mentioned degradable bone filling material in the preparation of medicines or preparations for treating bone defects.
[0035] The present invention has the following beneficial effects:
[0036] (1) The present invention provides a degradable bone filling material designed based on natural bone tissue, whose chemical composition and morphological structure are highly similar to the trabecular structure of the human body, and has the advantages of high mechanical strength, no biological toxicity and good biodegradability; in addition, it also has the effect of promoting bone formation, and can be completely absorbed and replaced by the patient's own bones in a short period of time, and is suitable for preparing drugs or preparations for treating bone defects and skeletal system diseases.
[0037] (2) The preparation process of the degradable bone filling material of the present invention is simple and low-cost. No cross-linking agent is required during the preparation process. The core skeleton structure with sufficient mechanical support performance is formed only by physical cross-linking and protein covalent binding, thereby avoiding the risks of cross-linking agents on the biocompatibility and safety of the material.
[0038] (3) The degradable bone filling material of the present invention has modular loading capability, which can realize modular drug delivery or adapt to different application requirements.
[0039] (4) The bone filling material of the present invention has the ability to carry cells in situ and can be used as a potential bone tissue organoid for different application needs such as bone defect treatment, drug screening and in situ inspection. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The microstructure diagram of the process of preparing the degradable bone filling material in Example 1; wherein A is a microstructure diagram of the organic collagen composed of silk fibroin, chitosan and base glue; B is a microstructure diagram of the core skeleton structure; C is a microstructure diagram of the porous skeleton structure; and D is a microstructure diagram of the degradable bone filling material;
[0041] Figure 2 It is the mechanical characterization diagram of different bone filling materials;
[0042] Figure 3 The diagram is a diagram showing the sustained release effect of degradable bone filling materials on small molecule drugs and nucleic acid drugs; wherein A is a diagram showing the sustained release effect of small molecule drugs; and B is a diagram showing the sustained release effect of nucleic acid drugs;
[0043] Figure 4 The figure is a result diagram of biosafety of degradable bone filling materials; A is a relative cell activity diagram; B is a relative cell cycle diagram; C is a hemolysis test result diagram; D is a hemolysis rate diagram;
[0044] Figure 5 Figure 1 is a diagram showing the regulatory effect of degradable bone filling materials on osteogenic differentiation; A is a diagram showing the staining results; B is a diagram showing the effect on the Alp expression level of hMSC; and C is a diagram showing the effect on the Runx2 expression level of hMSC;
[0045] Figure 6Figure 1 is a diagram showing the long-term regulatory effect of degradable bone filling materials on osteogenic differentiation through sustained-release drugs; A is a staining result diagram after 2 weeks of drug loading; B is a diagram showing the effect of drug loading on the Alp expression level of hMSC after 2 weeks of drug loading; C is a diagram showing the effect of drug loading on the Runx2 expression level of hMSC after 2 weeks of drug loading; D is a diagram showing the staining result diagram after 4 weeks of drug loading; E is a diagram showing the effect of drug loading on the Alp expression level of hMSC after 4 weeks of drug loading; F is a diagram showing the effect of drug loading on the Runx2 expression level of hMSC after 4 weeks of drug loading;
[0046] Figure 7 It is a modular modification function diagram of degradable bone filling materials; A is a thermosensitive phase change diagram of the hydrogel outside the degradable bone filling material; B is a diagram of the sustained release ability of nucleic acid drugs of the degradable bone filling material in the presence of nucleic acid targeting vectors; C is a diagram of biosafety results; D is a diagram of miR-381-3p expression level;
[0047] Figure 8 Figure 1 is a graph showing the activity and osteogenic differentiation level of hMSC cells carried by degradable bone filling materials; A is a graph showing the biosafety results of hMSC cells during in vitro culture; B is a graph showing the biosafety results of hMSC cells during in vivo culture; C is a graph showing the effect on the Alp expression level of hMSC; D is a graph showing the effect on the Runx2 expression level of hMSC;
[0048] Fig. 9 The effect of primary ADSCs on promoting osteogenesis in degradable bone filling materials is shown in Figure 1. AB shows the distribution of ADSCs in the material after 72 hours of in vitro culture. C shows the immunofluorescence staining of osteogenic marker genes of cells after 10 days of in vitro culture. D shows the immunofluorescence staining of osteogenic marker genes of cells after 10 days of implantation of the material into mice.
[0049] Fig.10 The figure is a diagram showing the therapeutic effect of degradable bone filling materials on tibial bone defects; A is a micro-CT result of mouse tibia; B is a bone density diagram; C is a relative bone volume diagram;
[0050] Fig.11 The figure is a graph showing the bone formation promotion of the degradable bone filling material on the skull bone defect; A is the calcein labeling result graph of the skull bone defect attachment area; B is the bone mineralization deposition rate graph;
[0051] Fig.12 The figures are diagrams showing the effect of degradable bone filling materials on fracture treatment; A is the micro-CT result of mouse tibia; and B is the relative bone volume diagram. DETAILED DESCRIPTION
[0052] The features and performance of the present invention are further described in detail below in conjunction with the examples, so that those skilled in the art can understand the present invention, but it should be clear that the present invention is not limited to the scope of the specific embodiments. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the present invention are protected. Unless otherwise specified, the reagents, instruments, etc. used in the present invention are all commercially available products.
[0053] Example 1
[0054] A method for preparing a degradable bone filling material comprises the following steps:
[0055] (1) 750 μL of 7% silk fibroin solution, 1000 μL of 2% chitosan solution and 1000 μL Corning 354480 base gel were mixed and 3 g of biphasic calcium phosphate was added, mixed under 65°C water bath heating conditions, frozen at -80°C for 30 min, and then freeze-dried at -80°C and a vacuum degree of 20 Pa. After being taken out and soaked in water for 2 min, the mixture was placed in a mold and freeze-dried again at -80°C and a vacuum degree of 20 Pa to obtain a core skeleton structure;
[0056] (2) Take 750 μL of 7% silk fibroin solution, 1000 μL of 2% chitosan solution containing 1% methacryloyl RGD peptide and 1000 μL of Corning 354480 base gel, mix well and add 3 g of biphasic calcium phosphate, mix well in a 65°C water bath and cover the core skeleton structure surface, freeze it at -80°C for 30 min, and then freeze it at -80°C and 20 Pa vacuum, take it out and soak it in water for 3 min, freeze it at -80°C for 30 min, and then freeze it at -80°C and 20 Pa vacuum to obtain a porous skeleton structure;
[0057] (3) The surface of the porous skeleton structure is covered with methacryloyl hyaluronic acid hydrogel to obtain a degradable bone filling material.
[0058] The silk fibroin solution with a mass concentration of 7% was prepared by the following steps: 3g of silk and 4.6g of anhydrous sodium carbonate powder were boiled in 6L of deionized water for 1h, washed with running water overnight, and dried; the silk was then dissolved in alcohol calcium chloride, and polyethylene glycol was added to precipitate it, and the obtained product was freeze-dried and dissolved in water to obtain a silk fibroin solution with a mass concentration of 7%;
[0059] A chitosan solution with a mass concentration of 2% was prepared by the following steps: 0.8 g of chitosan was added to 40 mL of deionized water, and then 160 μL of glacial acetic acid was added and magnetically stirred, and the chitosan solution with a mass concentration of 2% was obtained after stirring evenly;
[0060] The biphasic calcium phosphate is prepared by ultrasonically mixing hydroxyapatite powder and tricalcium phosphate powder in a mass ratio of 55:45.
[0061] This embodiment also provides a degradable bone filling material prepared by the above preparation method. The degradable bone filling material includes a core skeleton structure, a porous skeleton structure based on the core skeleton structure, and a hydrogel covered on the surface thereof.
[0062] The microstructure of the above-mentioned degradable bone filling material was observed by scanning electron microscopy (SEM). Figure 1 As shown in the preparation process, silk fibroin, chitosan, and base glue can form a shaped organic collagen ( Figure 1 Figure A, Organic), and after adding biphasic calcium phosphate, it can be extruded and rapidly freeze-dried to form a core skeleton structure ( Figure 1 The core skeleton is covered with the above mixture, then immersed in water and frozen and then freeze-dried to form a randomly distributed porous skeleton structure similar to trabeculae ( Figure 1 Middle C, Frame), and finally the surface is covered with HAMA hydrogel to encapsulate into a complete degradable bone filling material ( Figure 1 (D in the middle, Artificial bone).
[0063] Example 2
[0064] A method for preparing a degradable bone filling material comprises the following steps:
[0065] (1) 700 μL of 7% silk fibroin solution, 1000 μL of 2% chitosan solution and 1000 μL Corning 354480 base gel were mixed and 2 g of biphasic calcium phosphate was added, mixed in a 55°C water bath, frozen at -55°C for 60 min, and then freeze-dried at -80°C and a vacuum degree of 20 Pa. After being taken out and soaked in water for 1.5 min, the mixture was placed in a mold and freeze-dried again at -80°C and a vacuum degree of 20 Pa to obtain a core skeleton structure;
[0066] (2) Take 700 μL of 7% silk fibroin solution, 1000 μL of 2% chitosan solution containing 0.01% methacryloyl RGD peptide and 1000 μL of Corning 354480 base gel, mix well and add 2 g of biphasic calcium phosphate, mix well in a 55°C water bath and cover the core skeleton structure surface, freeze it at -55°C for 60 min, and then freeze it at -80°C and 20 Pa vacuum, take it out and soak it in water for 2 min, freeze it at -55°C for 60 min, and then freeze it at -80°C and 20 Pa vacuum to obtain a porous skeleton structure;
[0067] (3) The surface of the porous skeleton structure is covered with methacryloyl gelatin to obtain a degradable bone filling material.
[0068] The silk fibroin solution with a mass concentration of 7% was prepared by the following steps: 3g of silk and 4.6g of anhydrous sodium carbonate powder were boiled in 6L of deionized water for 1h, washed with running water overnight, and dried; the silk was then dissolved in alcohol calcium chloride, and polyethylene glycol was added to precipitate it, and the obtained product was freeze-dried and dissolved in water to obtain a silk fibroin solution with a mass concentration of 7%;
[0069] A chitosan solution with a mass concentration of 2% was prepared by the following steps: 0.8 g of chitosan was added to 40 mL of deionized water, and then 160 μL of glacial acetic acid was added and magnetically stirred, and the chitosan solution with a mass concentration of 2% was obtained after stirring evenly;
[0070] The biphasic calcium phosphate is prepared by ultrasonically mixing hydroxyapatite powder and tricalcium phosphate powder in a mass ratio of 55:45.
[0071] This embodiment also provides a degradable bone filling material prepared by the above preparation method. The degradable bone filling material includes a core skeleton structure, a porous skeleton structure based on the core skeleton structure, and a hydrogel covered on the surface thereof.
[0072] Example 3
[0073] A method for preparing a degradable bone filling material comprises the following steps:
[0074] (1) 800 μL of 7% silk fibroin solution, 1000 μL of 2% chitosan solution and 1000 μL Corning 354480 base gel were mixed and 4 g of biphasic calcium phosphate was added, mixed in a 75°C water bath, frozen at -200°C for 20 min, and then freeze-dried at -80°C and a vacuum degree of 20 Pa. After being taken out and soaked in water for 2 min, the mixture was placed in a mold and freeze-dried again at -80°C and a vacuum degree of 20 Pa to obtain a core skeleton structure;
[0075] (2) Take 800 μL of 7% silk fibroin solution, 1000 μL of 2% chitosan solution containing 1% methacryloyl RGD peptide and 1000 μL of Corning 354480 base gel, mix them and add 4 g of biphasic calcium phosphate, mix them in a 75°C water bath and cover them on the surface of the core skeleton structure, freeze them at -200°C for 20 min, and then freeze them at -80°C and 20 Pa vacuum, take them out and soak them in water for 15 min, freeze them at -200°C for 20 min, and then freeze them at -80°C and 20 Pa vacuum to obtain a porous skeleton structure;
[0076] (3) The surface of the porous skeleton structure is covered with a thermosensitive hydrogel to obtain a degradable bone filling material.
[0077] The silk fibroin solution with a mass concentration of 7% was prepared by the following steps: 3g of silk and 4.6g of anhydrous sodium carbonate powder were boiled in 6L of deionized water for 1h, washed with running water overnight, and dried; the silk was then dissolved in alcohol calcium chloride, and polyethylene glycol was added to precipitate it, and the obtained product was freeze-dried and dissolved in water to obtain a silk fibroin solution with a mass concentration of 7%;
[0078] A chitosan solution with a mass concentration of 2% was prepared by the following steps: 0.8 g of chitosan was added to 40 mL of deionized water, and then 160 μL of glacial acetic acid was added and magnetically stirred, and the chitosan solution with a mass concentration of 2% was obtained after stirring evenly;
[0079] The biphasic calcium phosphate is prepared by ultrasonically mixing hydroxyapatite powder and tricalcium phosphate powder in a mass ratio of 55:45.
[0080] This embodiment also provides a degradable bone filling material prepared by the above preparation method. The degradable bone filling material includes a core skeleton structure, a porous skeleton structure based on the core skeleton structure, and a hydrogel covered on the surface thereof.
[0081] Example 4 Mechanical Characterization of Degradable Bone Filling Materials
[0082] Bone filling materials need to have certain supporting and compressive properties. In this example, the elastic moduli of four groups of materials, namely, blank methacryloyl hyaluronic acid (HAMA) hydrogel, HAMA (core) wrapped only in the core skeleton structure, HAMA (peripheral) wrapped only in the porous skeleton structure, and the degradable bone filling material (Artificial bone) prepared by the present invention, were measured. The results are as follows: Figure 2 As shown. Figure 2It can be seen that the addition of the core skeleton structure significantly improves the compressive resistance of HAMA, and the degradable bone filling material has better elasticity and material strength than the other groups, which can meet the mechanical load-bearing requirements of bone tissue and is expected to be used as a potential bone filling material.
[0083] Example 5 Sustained release effect of degradable bone filling materials on small molecule drugs and nucleic acid drugs
[0084] A HAMA hydrogel (rhodamine B: 5 μg / mL, FAM-NC: 100 μM, SSAD / HA: 100 μL) was prepared using a solution containing a fluorescent marker, and a degradable bone filling material was prepared according to the method of Example 1. The prepared degradable bone filling material was immersed in deionized water for 30 minutes, then immersed in deionized water and placed at 4°C for sustained release; the HAMA hydrogel containing only rhodamine B was placed at room temperature for sustained release; after collecting the sustained release solution at different time points, the degradable bone filling material was immersed in deionized water again for continued sustained release; the fluorescence intensity was measured using a multifunctional microplate reader to evaluate the sustained release effect of the degradable bone filling material on small molecule drugs and nucleic acid drugs.
[0085] The fluorescent dye Rhodamine B was used to detect the sustained release characteristics of small molecule drugs. Figure 3 As shown. Figure 3 As can be seen from Figure A, the degradable bone filling material has a certain ability to carry and release small molecule drugs; Figure 3 As can be seen from Figure B, the degradable bone filling material can slowly release FAM-modified siRNA-NC when the nucleic acid delivery carrier PVAm is added, indicating that it has an enhanced ability to carry and slowly release nucleic acids for a long time, and still has a sufficiently high carrying capacity on the 14th day. This result shows that the degradable bone filling material has a certain ability to carry and slowly release small molecule drugs and nucleic acid drugs, and is expected to become a bone filling material that promotes osteogenesis and treats bone defects.
[0086] Example 6 Biosafety of Degradable Bone Filling Materials
[0087] The degradable bone filling material was placed in human mesenchymal stem cell (hMSC) culture medium and co-cultured with the cells to detect the cell proliferation rate. The results are as follows Figure 4 As shown, Blank represents untreated cells, Artificial bone represents cells treated with the degradable bone filling material prepared in Example 1 of the present invention, HAMA represents cells treated with methacryloyl hyaluronic acid, and Triton represents a positive control (Triton X-100). Figure 4 It can be seen that the degradable bone filling material has no effect on the cell proliferation rate (such as Figure 4Cell cycle analysis showed that the cell cycle ratio of cells treated with the biodegradable bone filler material did not change compared with untreated cells and HAMA-treated cells (Fig. Figure 4 Hemolysis tests also showed that degradable bone filling materials do not cause hemolysis (e.g. Figure 4 CD). This demonstrates that the material has good in vitro biosafety.
[0088] Example 7 Ability of Degradable Bone Filling Material to Promote Osteogenic Differentiation after Loading Drugs
[0089] The small molecule drug bergamotrin and the nucleic acid drug recombinant antagomiR-138 (anti138) were introduced into the degradable bone filling material, and the material was co-cultured with hMSCs in the logarithmic growth phase. The expression levels of Alp and Runx2 were detected by qPCR, the level of mineralized nodules was detected by alizarin red staining, and the activity of cell alkaline phosphatase was detected by alkaline phosphatase staining. The results are as follows Figure 5 shown. Figure 5 The results showed that after the introduction of small molecule drug bergamotin and nucleic acid drug recombinant antagomiR-138, the degradable bone filling material could promote the expression levels of Alp and Runx2 of hMSC, the level of mineralized nodule formation and alkaline phosphatase activity, indicating that the degradable bone filling material can promote cell osteogenic differentiation after being loaded with drugs.
[0090] Example 8 Ability of Degradable Bone Filling Material to Sustained Release Drugs to Promote Osteogenic Differentiation of Cells
[0091] The sustained-release liquid of the degradable bone filling material carrying the small molecule drug bergamotrin and the nucleic acid drug recombinant antagomiR-138 was extracted at different time points, and the hMSCs were transfected with the liquid to detect the ability of the sustained-release liquid to promote cell osteogenic differentiation, thereby detecting the sustained-release ability of the degradable bone filling material. The results are as follows Figure 6 shown. Figure 6 The results showed that after the degradable bone filling material was loaded with drugs for 4 weeks, it was still able to promote the osteogenic differentiation of hMSCs through a sustained release effect, proving that the degradable bone filling material prepared by the present invention has the ability to sustain drug release.
[0092] Example 9 Modular modification of degradable bone filling materials
[0093] By adding less than 30% of DNA self-assembly material into the peripheral HAMA hydrogel of the degradable bone filling material (Li Z, et al, J Am Chem Soc, 2019), the peripheral hydrogel is cross-linked to become a thermosensitive hydrogel material, which is solid at 35°C, close to the biological body temperature, and becomes a viscous liquid at 45-55°C due to the denaturation of the DNA material (such as Figure 7 The degradable bone filling material can maintain the sustained release of nucleic acid drugs for about 2 weeks in the presence of nucleic acid targeting vectors (e.g. Figure 7 B), and also has good in vitro and in vivo biosafety (such as Figure 7 Figure C). Degradable bone filling materials modified with thermosensitive hydrogel and nucleic acid targeting vector were implanted subcutaneously in the skull and in the femoral bone marrow of mice. The results showed that the degradable bone filling materials can accurately deliver nucleic acid drugs to bone tissue (e.g. Figure 7 (Fig. D).
[0094] Example 10 Ability and biosafety of degradable bone filling materials as bionic organoids
[0095] The biodegradable bone filling material was used to carry hMSC cells, the small molecule drug bergamotin that promotes cell osteogenic differentiation, and the nucleic acid drug recombinant antagomiR-138. In vitro osteogenic culture was performed in a culture dish, and the cell activity and cell osteogenic differentiation level carried by the biodegradable bone filling material were detected. The results are as follows Figure 8 shown. Figure 8 The results showed that hMSCs can grow normally in degradable bone filling materials regardless of whether the materials are implanted in mice or cultured in vitro, and when the materials are simultaneously loaded with nucleic acid drugs or small molecule drugs, the osteogenic differentiation ability of the cells will also be affected; this indicates that degradable bone filling materials have the potential to serve as bionic bone tissue organoids.
[0096] Example 11 Possibility of using degradable bone filling materials to carry cells as organoids
[0097] Primary mouse adipose-derived mesenchymal stem cells (ADSCs) were embedded in degradable bone filling materials and cultured in a flow medium. Fig. 9 As shown, ACTIN represents β-Actin (cytoskeletal protein), ALP represents alkaline phosphatase, and RUNX2 represents Runt-related transcription factor 2. Fig. 9 The results showed that the degradable bone filling material can support the growth of cells within its skeleton structure; at the same time, the degradable bone filling material maintains the potential for migration and differentiation; the in vivo experiments in mice also proved this conclusion. This shows that the degradable bone filling material can embed cells without affecting the physiological properties of the embedded cells.
[0098] Example 12 The therapeutic effect of degradable bone filling materials on bone defect mice
[0099] A mouse model of skull and tibia bone defects was constructed, and the small molecule drug bergamotrin and recombinant antagomiR-138 were locally implanted into the bone defects of the mouse skull and tibia by introducing degradable bone filling materials, respectively, to study their effects on the repair of mouse bone defects.
[0100] from Fig.10 The micro-CT results of the mouse tibia showed that the biodegradable bone filling material had a significant filling effect on the bone defect site, and after adding bergamot and recombinant antagomiR-138, it played a significant role in promoting the repair of the bone defect site. Fig.11 The results of calcein labeling in the accessory area of the mid-skull bone defect showed that the bone formation rate in the bergamotrin and recombinant antagomiR-138 groups was significantly increased, proving that the degradable bone filling material can carry and deliver drugs, thereby promoting bone repair.
[0101] Example 13 The therapeutic effect of degradable bone filling materials on fractures
[0102] A mouse model of tibial fracture was constructed. The small molecule drug bergamotrin and recombinant antagomiR-138 were introduced into the fracture end of the mouse tibia through the introduction of degradable bone filling materials, and their effects on tibial bone formation in mice were studied. The results are as follows: Fig.12 shown. Fig.12 Micro-CT results showed that both bergamotrin and recombinant antagomiR-138 groups had a significant promoting effect on fracture repair, proving that the degradable bone filling material can carry and deliver drugs, thereby playing a role in treating fractures.
[0103] The present invention has been described according to the above embodiments. It should be understood that the above embodiments do not limit the present invention in any form. Any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the scope of the present invention.
Claims
1. A method for preparing a degradable bone filling material, characterized in that: The following steps are involved: (1) mixing the silk fibroin solution, chitosan solution and base glue and adding biphasic calcium phosphate, mixing under heating conditions and then freezing and freeze-drying, taking out and soaking in water and placing it in a mold and freeze-drying again to obtain a core skeleton structure; (2) separately taking a silk fibroin solution, a chitosan solution containing methacryloyl RGD peptide and a base gel, mixing them evenly and adding biphasic calcium phosphate, mixing them evenly under heating conditions, covering the surface of the core skeleton structure, and freezing and freeze-drying them in sequence, taking them out and soaking them in water, freezing and freeze-drying them again, so as to obtain a porous skeleton structure; (3) The surface of the porous skeleton structure is covered with hydrogel to obtain a degradable bone filling material.
2. The method for preparing the degradable bone filling material according to claim 1, characterized in that: The mass concentration of the silk fibroin solution in step (1) and step (2) is 6-8%; the mass concentration of the chitosan solution in step (1) is 1-3%; the mass concentration of the chitosan solution containing methacryloyl RGD peptide in step (2) is 1-3%.
3. The method for preparing the degradable bone filling material according to claim 1 or 2, characterized in that: In the step (1), the material-liquid ratio of the silk fibroin solution, the chitosan solution, the base glue and the biphasic calcium phosphate is 0.7-0.8 mL: 1 mL: 1 mL: 2-4 g; in the step (2), the material-liquid ratio of the silk fibroin solution, the chitosan solution containing the methacryloyl RGD peptide, the base glue and the biphasic calcium phosphate is 0.7-0.8 mL: 1 mL: 1 mL: 2-4 g; the mass concentration of the methacryloyl RGD peptide in the chitosan solution containing the methacryloyl RGD peptide is 0.01-1%.
4. The method for preparing the degradable bone filling material according to claim 1, characterized in that: The step (1) comprises the following steps: mixing the silk fibroin solution, chitosan solution and base glue and adding biphasic calcium phosphate, mixing under heating conditions of 55-75°C in a water bath, freezing at -55--200°C for 20-60 minutes and then freeze-drying, taking out and soaking in water for 1.5-2 minutes, placing it in a mold and freeze-drying it again to obtain a core skeleton structure.
5. The method for preparing the degradable bone filling material according to claim 1, characterized in that: The step (2) comprises the following steps: separately taking a silk fibroin solution, a chitosan solution containing methacryloyl RGD peptide and a base glue, mixing them and adding biphasic calcium phosphate, mixing them in a water bath at 55 to 75° C. and covering the mixture on the surface of the core skeleton structure, freezing the mixture at -55 to -200° C. for 20 to 60 minutes and then freeze-drying the mixture, taking the mixture out and soaking it in water for 2 to 15 minutes, freezing the mixture again at -55 to -200° C. for 20 to 60 minutes and then freeze-drying the mixture, thereby obtaining a porous skeleton structure.
6. The method for preparing the degradable bone filling material according to claim 1, characterized in that: The hydrogel in step (3) is a hydrogel that can carry and / or slowly release nucleic acid drugs, small molecule drugs, or can allow cells to grow, crawl, adhere, and migrate in a directional manner.
7. A degradable bone filling material prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the degradable bone filling material according to claim 7 in preparing bone tissue organoid materials.
9. Use of the degradable bone filling material according to claim 7 in the preparation of medicines or preparations for treating skeletal system diseases.
10. Use of the degradable bone filling material according to claim 7 in the preparation of a medicine or preparation for treating bone defects.
Citation Information
Patent Citations
Bone-grafting filling material and preparation method thereof
CN103800944A
Bone tissue engineering scaffold material and preparation method thereof
CN104984393A
Osteochondral repairing biphasic porous composite stent and preparation method thereof
CN106178126A
Preparation method for biphasic calcium phosphate plural gel
CN108478873A
Nanometer hydroxyapatite / chitosan porous composite scaffold material as well as bionic dialysis mineralization preparation method and application thereof
CN108478880A